2016
DOI: 10.1007/s11356-016-7457-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of nitrate transport parameters using the advection-diffusion cell

Abstract: This study aimed to better understand nitrate transport in the soil system in a part of the state of North Rhine-Westphalia, in Germany, and to aid in the development of groundwater protection plans. An advection-diffusion (AD) cell was used in a miscible displacement experiment setup to characterize nitrate transport in 12 different soil samples from the study area. The three nitrate sorption isotherms were tested to define the exact nitrate interaction with the soil matrix. Soils varied in their properties w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
3
2
0
Order By: Relevance
“…This could be attributed to the disinfection process that has been performed on the equipment used. This result is consistent with what was found in a previous study [21] that reported that if no biological inhibitor was added, then the nitrate flux decreased after a short time of test and that refers to the phenomenon of the formation of a microbial film that consumes nitrate as a growth media and causes some biological reduction.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…This could be attributed to the disinfection process that has been performed on the equipment used. This result is consistent with what was found in a previous study [21] that reported that if no biological inhibitor was added, then the nitrate flux decreased after a short time of test and that refers to the phenomenon of the formation of a microbial film that consumes nitrate as a growth media and causes some biological reduction.…”
Section: Resultssupporting
confidence: 93%
“…Furthermore, a higher concentration of nitrate solution entering the soil specimen in the ODC does not necessarily mean that soil specimens will spend less time to reach equilibrium state [34,47], hence the sorbed amount of nitrate is higher; the enclosed area between the two curves is bigger. This finding is directly in line with what is stated by Aljazzar and Al-Qinna [21], who named the plotted area between the two nitrate fluxes as a confined area representing the amount of nitrate adsorbed within the soil sample and thus indicating nitrate retardation in each sample.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The combination of these processes is a key factor in changes of nitrate concentration in the soil-water system. Aljazzar & Al-Qinna (2016) reported that nitrate transport in coarsely textured soils was dominated by advection supported by low sorption capacity, while nitrate transport in loamy soils was primarily through diffusion. Moreover, it was detemined in our laboratory studies that cohesive soils tended to adsorb nitrate onto their surface.…”
Section: Layermentioning
confidence: 99%